Physical mapping of the Mycoplasma pneumoniae genome. - Wenzel, R (1988)
In order to study the genome organization of Mycoplasma pneumoniae a cosmid library of M. pneumoniae DNA was established using a newly designed cosmid vector (pcosRW2). From this library 32 overlapping clones were isolated covering a contiguous 720 kbp DNA segment representing about 90% of the genome assuming a genome size of about 800 kbp.